Desenho e implementação de um curso de francês a distância sob o viés da complexidade - Silva, Bárbara Szuparits (2014)
This work research aims at describing and interpreting, from hermeneutical-phenomenological approach, the experience lived by me, teacher-researcher, throughout preparing, executing and reflecting on a distance French course, offered on a virtual learning setting, conceived in the light of Complexity theory (MORIN, 1982, 1990, 2000, 2003a, 2003b), aided by "Complex Educational Design" (FREIRE, 2013); this experience was taken as a phenomena. Besides this, my intention is describing and interpreting the experience lived by students who have taken part on this course, named Francês Módulo I. In addition to Complexity theory, some theoretical issues concerning to Distant Education and Teaching and Learning French as a Foreigner Language and as well as to the CED, Complex Educational Design, were taken into account as background for this research. Out of 14 undergraduate students, who have started the Online French course, only 8 have finished it for several reasons. Over the time course, texts (research tools) were written for different purposes (questionnaires, diaries, forums, e-mail messages, video conferences, hermeneutical conversations and Facebook posts) and they allowed me to identify the themes which constitute the essence of the studied phenomena, from the methodological orientation chosen. It was possible for me to present my interpretations about the lived experiences, making them clear to the reader about challenges not only faced by me as a teacher-researcher but also by the students who were enrolled on this course; mainly on three topics: interests, possibilities and motivation. Finally, I bring to the reader my (in)conclusions in which I give an overview about relevant aspects for those teachers who intend to work at distance taking into account Complexity lens